Educational and Career Goals of Pharmacy Students Upon Graduation - Migliore, Mattia M. (American Journal of Pharmaceutical Education, 2013)
Objective. To assess the doctor of pharmacy (PharmD) students’ desire to obtain additional degrees after graduation. Methods. During the spring 2011 semester, an anonymous 14-question survey instrument was administered to students across all 6 years of the PharmD program to evaluate their interest in obtaining an additional degree after graduation. Demographic data was also collected and analyzed from this convenience sample. Results. Approximately 34% of the respondents (n=1,239) indicated a desire to seek an additional degree. Of the additional degrees offered in the survey instrument, more than one-third of the students expressed interest in the master of business administration (MBA). Also, 79% of those respondents were willing to take summer courses to achieve a dual or additional degree. Conclusion. Pharmacy students are interested in obtaining an additional degree(s) after graduation and are willing to complete summer courses to achieve their career goals.